Current status of bat diversity and conservation in Universiti Putra Malaysia and its forest reserves - Mohd Top @ Mohd Tah, Marina; Chubo, John Keen; Senawi, Juliana; Johari, Nur Farrazuin; Abdul Rahim, Ahmad Badrul Amin (Universiti Malaysia Terengganu, 2021)
Universiti Putra Malaysia consists of three main areas, namely Serdang main campus in Selangor (UPMSC), Bintulu campus in Sarawak (UPMKB) and the UPM forest in Ayer Hitam Forest Reserve (AHFR) in Puchong, Selangor, which are all managed by the university. This article compiles available information regarding bats in UPM besides updating the available list of bat species from published and unpublished papers, and recent sampling using harp traps and mist nets. A total of 36 bat species were reported in UPM (12 species in UPMSC, 20 species in UPMKB and 21 species in AHFR). These bats were from seven families: Emballonuridae (three species), Hipposideridae (four species), Megadermatidae (one species), Nycteridae (one species), Pteropodidae (13 species), Rhinolophidae (two species) and Vespertilionidae (12 species). With regards to the conservation status, one species (Hypsugo macrotis) is categorised as ‘Data Deficient’, five species (Dyacopterus spadiceus, Kerivoula intermedia, K. minuta, Nycteris tragata, and Rhinolophus sedulus) as ‘Near Threatened’ and one species (Megaerops albicollis) categorised as ‘Vulnerable’ on the IUCN Red List of Threatened Species. The list of bat species provided, including those with conservation importance, can serve as a reference for campus management practices on its environmental activities especially in enhancing biodiversity value within the campus area.